Penerapan Konsep Pewarnaan Graf Dalam Penyusunan Jadwal Kegiatan Belajar Mengajar Di SMKN - Laili Gadis Hasanah; Sripatmi Sripatmi; Amrullah Amrullah; Baidowi (Griya Journal of Mathematics Education and Application, 2022)
The problem of scheduling learning activities at SMKN 4 Mataram is the same teachers are scheduled at the same time in two class or more. The coloring graph concept can be used to find out the causes of the scheduling problems at SMKN 4 Mataram. Based on result of the application coloring graph concept generated to the chromatic number is 23 with slots number is 46 which is smaller than 55 or time slots at SMKN 4 Mataram. Because slots of chromatic number are smaller than the time slots at SMKN 4 Mataram, it is known that the causes of scheduling problems at SMKN 4 Mataram are wrong scheduling way. One of solution to this problem is to compile a schedule based on the coloring graph concept by mapping 419 subjects with 84 teachers and 55 time slots spread from Monday to Saturday. In applying the coloring graph concept, the Largest Degree Ordering (LDO) algorithm is used. It is because this algorithm is simpler than other algorithms.